Thermal and mechanical properties of treated and untreated Red Balau (Shorea Dipterocarpaceae)/LDPE composites - Lafia-Araga, R.A.; Hassan, A.; Yahya, R.; Rahman, N.A.; Hornsby, P.R.; Heidarian, J. (2012)
Red Balau saw dust was heat-treated at 180Â°C and 200Â°C for 1 h. Treated and untreated wood flour were compounded with LDPE at 9, 20, and 37 by weight and molded in an injection molding machine. Thermal and mechanical properties of the resultant composites were investigated as a function of filler loadings and treatment temperature. Thermogravimetric analysis revealed an increase in degradation peak temperature (T p) of the heat-treated wood and composites. DSC revealed a decreasing trend in the degree of crystallinity (X c) of the matrix when heat-treated wood was used as filler. On the other hand, untreated wood showed an increase in X c with increasing wood content. Tensile modulus increased with heat treatment and filler loading. Furthermore, flexural strength and modulus were found to increase with filler loading.